2016
DOI: 10.22610/jebs.v8i5(j).1431
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Chaos on the Johannesburg Stock Exchange

Abstract: This study investigates the existence of chaos on the Johannesburg Stock Exchange (JSE) and studies three indices namely the FTSE/JSE All Share, FTSE/JSE Top 40 and FTSE/JSE Small Cap. Building upon the Fractal Market Hypothesis to provide evidence on the behavior of returns time series of the above mentioned indices, the BDS test is applied to test for non-random chaotic dynamics and further applies the rescaled range analysis to ascertain randomness, persistence or mean reversion on the JSE. The BDS test sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Sarpong et al (2016) found H ¼ 0:46 for the JSE using daily data from 1995 to 2015 (thereby embracing the full period investigated by Chimanga and Mlambo, 2014). In addition, Sarpong et al (2016) used the BDS test (Brock et al, 1996) to verify that JSE price index data exhibit non-random chaotic dynamics rather than pure randomness. These results confirm those obtained by Smith (2008) using four joint variance ratio tests, rejected the random walk hypothesis on the JSE.…”
Section: Empirical Evidence Sourcesmentioning
confidence: 77%
See 1 more Smart Citation
“…Sarpong et al (2016) found H ¼ 0:46 for the JSE using daily data from 1995 to 2015 (thereby embracing the full period investigated by Chimanga and Mlambo, 2014). In addition, Sarpong et al (2016) used the BDS test (Brock et al, 1996) to verify that JSE price index data exhibit non-random chaotic dynamics rather than pure randomness. These results confirm those obtained by Smith (2008) using four joint variance ratio tests, rejected the random walk hypothesis on the JSE.…”
Section: Empirical Evidence Sourcesmentioning
confidence: 77%
“…Smith (2008) also found statistically significant results that H < 0:5, but over a shorter horizon and using daily (rather than monthly) data. Sarpong et al (2016) using daily JSE index data spanning 20 years from 1995 to 2015 also found H < 0:5 prior to 2012 and H % 0 after 2012. The South African market was also found to be more "sectorized" or heterogenous with respect to H; different market sectors are characterized by different values of H and these values tend to persist over time.…”
Section: Hurst Exponent Hmentioning
confidence: 88%
“…Affleck-Graves and Money (1975) subsequently presented findings that contradicted the study mentioned above, providing evidence supporting the weak form of efficiency. According to recent research conducted by Sarpong et al (2016), it has been argued that small-cap companies receive less attention or are completely overlooked by a significant number of analysts and investors. Consequently, the market for small stocks tends to exhibit inefficiencies compared to their large-cap counterparts, resulting in prices deviating from their fair values.…”
Section: Efficient Market Hypothesis (Emh)mentioning
confidence: 99%